Evaluation of the preventive effects of alligator pepper aframomum melegueta aqueous extract against titanium dioxide nanoparticles induced oxidative stress in adult wistar rats - Al-Asady, Fatima H.; AL-Mohanna, Mohammed W.H. (International Journal of Advanced Chemistry, 2024)
This study evaluated the potential protective effects of Alligator pepper Aframomum melegueta (AM) seeds' aqueous extract in adult Wistar rats treated with Titanium Dioxide Nanoparticles (Tio2NP). The study included the preparation of an A. melegueta aqueous extract of AP. Thirty-six healthy adult male Wistar rats were used, randomly distributed into six groups containing six rats, each dosed orally for 60 consecutive days; group 1: control group (5ml b.w. distilled water only: Group 2:100 mg/kg TIO2 NP suspension). Group 3:100mg/kg AM Aqueous extract). Group 4: 200 mg/kg AM Aqueous extract). Group 5:100 mg/kg b.w. AM before 4 hours receive TIO2 NP 100 mg/kg b.w.). Group 6:200 mg/kg b.w AM Aqueous extract before four h receive TIO2 NP 100 mg/kg b.w.The study results revealed that Restoring normal levels of blood lipid profile in G5andG6 is represented by a significant p < 0.05 decrease in the level of cholesterol, LDL accompanied by a significant p < 0.05 increase in the level of HDL compared to the Tio2NP group. A. melegueta aqueous extract 100 and 200 mg/kg was highly protected from the toxicity of TIO2 NP in Wistar rats by a significant p < 0.05 increase of SOD and Catalase level and p < 0.05 decreased MDA. The study suggested that when taken orally, the aqueous extract of AM seeds improves the defense against adverse effects of Tio2NP that cause oxidative stress and change the lipid profile, depending on the dose.